BTEC National Children's Care, Learning + Development. Book 1 - Green, Sandy (Cheltenham : Nelson Thornes, 2007)
Written in a clear and accessible style, this book is packed with engaging activities and case studies, enabling you to relate the theory of caring for and working with children to real life situations.
Includes bibliographical references (p. 457-460) and index.
Keywords: Child care -- Examinations -- Study guides; Child development -- Examinations -- Study guides; Society